Kinetics and mechanisms for ion-assisted etching of InP thin films in HBr + Cl-2 + Ar inductively coupled plasma with various HBr/Cl-2 mixing ratios - Kim, Changmok; Efremov, Alexander; Lee, Jaemin; Han, Il Ki; Kim, Young-Hwan; Kwon, Kwang-Ho (ELSEVIER SCIENCE SA, 2018)
The study of InP etching kinetics as well as the evaluation of InP etching mechanism in HBr+Cl-2+Ar inductively coupled plasma were carried out. Experiments on the measurements of the etching rates for InP, SiO2, and SiNx as well as plasma diagnostics using Langmuir probes and optical emission spectroscopy were conducted at a fixed total gas pressure (10 mTorr, or 1.33 Pa), input power (800 W), and bias power (200 W), and the variable parameter was the HBr/Cl-2 mixing ratio. Zero-dimensional (global) plasma modeling provided data regarding the densities of the plasma active species as well as on the particle and energy fluxes to the etched surface. An increase in the Cl-2 fraction in the feed gas yielded a non-monotonic InP etching rate with a maximum of similar to 120 nm/min at 35% Cl-2. Model-based analysis of the InP etching kinetics revealed that 1) the InP etching process is mainly provided by the chemical etching pathway; 2) the non-monotonic change in the InP etching rate cannot be explained by the chemical effects of Br and Cl atoms; and 3) the HCl molecules may have sufficiently contributed to the chemical etching pathway.
Keywords: INDUCTIVELY-COUPLED PLASMA; III-V SEMICONDUCTORS; BCL3-BASED CHEMISTRIES; SURFACE KINETICS; PART I; GAAS; PRODUCTS; ALGAAS; CL-2; AR